#1**+8 **

Alright so first let's look at what we have.

First work away the brackets, for example;

$$3(x-4) = 6(2x+1) \Rightarrow 3x-12 = 12x+6$$

Now substract $$12x$$ from both sides

$$-9x-12 = 6$$

Add $$12$$ to both sides

$$-9x = 18$$

Divide both sides by -9

$$x = -2$$

voila!

reinout-g
May 27, 2014

#2**+8 **

Best Answer

3(x-4)=6(2x+1)

so now first well multiply 3 by x and 4 and 6 by 2x and 1 .

3x-12=12x+6

-6-12=12x-3x

-18=9x

-18/9=x

x=-2

rosala
May 27, 2014

#4**0 **

ur right reinout-g , first i did it ur way like my last step was -9=18

but then i didnt do it this way ! ah now ill never ever take chances as they always turn out scaaaaaaaarrrry !

rosala
May 27, 2014

#5**+3 **

Hi Rosala,

Reinout is right!

Use your edit button to fix your post (minus signs are missing)

also get rid or the extra = signs at the beginning of your lines and then I'll give you thumbs up!

Melody
May 27, 2014

#9**0 **

It would be even better Rosala if you deleted the equal signs at the begining of each line.

There should only be one equal sign per line!

Oh Reinout - I love your rooster - he is VERY talented!

Melody
May 27, 2014